Urban encounters affirmative action and black identities in Brazil - Cicalo, André 1973- (Palgrave Macmillan, 2012)
"In this work, I discuss the introduction of racial quotas in favor of 'black' students in some public universities of the State of Rio de Janeiro. The implementation of racial policies has raised strong reaction in a country like Brazil, where ideals of racial and cultural mixture are crucial components of national identity. Focusing on my ethnographic study of a public university and its users, I analyze the practical and symbolic potential that affirmative action has to redress historically-produced and territorialized inequalities in the urban space. Due to the variety of users that racial and other social quotas have produced, the ethnography allows for a broader discussion of race and class relations in Rio de Janeiro and in Brazil"--